👤

Folosind regula am an = am+n, calculează: a) (-3)³-(-3)²; c) (-5)-(-5)-(-5)4; 4. Folosind regula am: a = am-n, calculează: a) (-3)4: (-3)²; d) 32125:32124 5. Folosind regula (a - b) = a. b, calculează: a) [(-2) - (+3)]³; d) [(-2)-7]0; b) (+7)^: (+7)³; e) (-13)5: (-13); 6. Folosind regula a": b = (a: b)", calculează: a) 17²: (-17)²; d) (324)²: (-18)²; a) [(-2)2]4; d) (139)¹; b) (+7).(+7)³; d) (-4)¹-(-4)²-(-4)³-(-4)º. b) [3-(-5)]²; e) [(-13) 11 (-7)]¹; Folosind regula (am)n = amn, calculează: b) (5¹)⁰; e) (3²)³; b) (-25)³: (-5)³; e) (1331)³: (-121)³; c) 1124: 1122; f) (-1) 84: (-1) 13. c) [5-(-2)]³; f) [(-4) (-1)-233³. c) (-361)²:19²; f) (123)¹5: (-123) ¹5. c) [(-2)³]²; f) [(-1)5]¹².va rog repede dau coroană ❤️ ​

Răspuns :

1. Folosind regula \(a^m \cdot a^n = a^{m+n}\):

a) \((-3)^3 - (-3)^2 = (-3)^2 \cdot (-3 - 1) = 9 \cdot (-4) = -36\).

4. Folosind regula \(a^m \div a^n = a^{m-n}\):

a) \((-3)^4 \div (-3)^2 = (-3)^{4-2} = (-3)^2 = 9\).

5. Folosind regula \((a - b)^n = a^n - b^n\):

a) \([(-2) - (+3)]^3 = (-5)^3 = -125\).

6. Folosind regula \(\frac{a^m}{b^m} = (\frac{a}{b})^m\):

a) \((17)^2 \div (-17)^2 = (\frac{17}{-17})^2 = (-1)^2 = 1\).

7. Folosind regula \((a^m)^n = a^{m \cdot n}\):

a) \((5^1)^0 = 1^0 = 1\).

9. Folosind regula \((a \cdot b)^n = a^n \cdot b^n\):

a) \((-25)^3 \div (-5)^3 = (-25 \div -5)^3 = (-5)^3 = -125\).

11. Folosind regula \((a^m)^n = a^{m \cdot n}\):

c) \((-361)^2 \div 19^2 = (-361)^{2 \cdot 2} = (-361)^4\).

13. Folosind regula \((a - b)^n = a^n - b^n\):

c) \([(-2)^3]^2 = (-8)^2 = 64\).